Co-secretion of carboxypeptidase H and insulin from isolated rat islets of Langerhans. - Guest, P C (1989)
The release of carboxypeptidase H activity from isolated rat islets was determined and compared to the secretion of immunoreactive insulin. Analysis of pancreatic islet cells sorted into beta and non-beta types indicated that approx. 80% of islet carboxypeptidase H activity is present in the beta cell. The release of both insulin and carboxypeptidase H was stimulated markedly by increasing the glucose concentration in the medium from 2.8 to 28 mM. The fractional release was in accordance with the observed cellular distribution of both proteins. The secretory response was biphasic with time, with an initial rapid transient phase of release within 5 min, followed by a more sustained response. The concentration-dependencies of glucose stimulation of release of insulin and carboxypeptidase H were similar, with a threshold for stimulation around 5.6 mM-glucose and maximal stimulatory response at 16.7-28 mM-glucose. The release of both proteins was inhibited by 20 mM-mannoheptulose, removal of Ca2+ from the medium and addition of 1 microM-noradrenaline. The combination of 10 mM-4-methyl-2-oxopentanoate and 10 mM-glutamine stimulated the release of carboxypeptidase H and insulin, as did 3-isobutyl-1-methylxanthine and 350 microM-tolbutamide in the presence of glucose. It is evident that carboxypeptidase H is released from the pancreatic beta-cell by an exocytotic process from the same intracellular compartment as insulin. The release of carboxypeptidase H by a constitutive process was at best equivalent to 0.4%/h, or less than 2% of the maximal rate of release via the regulated pathway. It is concluded that carboxypeptidase H can be used as a sensitive index of beta-cell secretion and an alternative marker to the insulin-related peptides.